The Christmas craft book : 30 fun & festive projects to make with kids - Minter, Laura; Williams, Tia, 1982- (The Guild of Master Craftsman Publications, 2021)
The Christmas Craft Book is a festive collection of 30 fun projects using everyday recycled materials and craft supplies.--